Effects Of Accounting Information System And Employee Integrity On Employee Performance (Case Study At The Finance Department Of Telkom University). - Ali, Muhammad; Tarmidi, Didi; Kohar Mudzakar, Mochamad (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the influence of the accounting information system and employee integrity on employee performance. This study uses primary data in the form of a questionnaire distributed to employees of finance at Telkom University. The research method used is the descriptive verification method. Descriptive analysis is used to determine the description of the response value of respondents to each of the variables that have been determined. Data analysis to determine the causality relationship in this study, using multiple linear regression analysis. The results of this study indicate that both partially and simultaneously, the accounting information system and employee integrity have a positive effect on employee performance.